Analisis Kecurangan Laporan Keuangan dalam Perspektif Teori Fraud Hexagon pada Perusahaan Industri Keuangan yang Terdaftar di Bursa Efek Indonesia Tahun 2017-2022 - Rahma Dewi; Elvira Luthan (Al-Kharaj : Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2023)
This study aims to prove and verify the potential for Fraudulent Financial Reporting (FFR) based on the hexagon fraud theory. FFR practices cause losses to investors, creditors and other stakeholders, so it is important to identify the elements that trigger FFR practices. The elements of the hexagon fraud theory are stimulus, capability, collusion, opportunity, rationalization and ego in influencing the occurrence of FFR. Companies in the financial industry listed on the IDX 2017-2022 as the population in this study with a total of 95 companies. The sampling technique used purposive sampling and produced 55 companies as research samples. The research approach used is a quantitative approach. The data analysis technique used is SEM-PLS which is processed with the SmartPLS Vs 3.0 program. The findings in this study indicate that stimulus, capability, ego and collusion have a negative effect on FFR while there is no opportunity and rationalization effect on FFR. The results of this study contribute to academics in broadening references regarding factors triggering the occurrence of FFR, as well as adding insight to companies in detecting FFR as an effort to improve the company's control system and as a tool for potential investors in analyzing their investments to reduce the risk of loss